Axons-on-a-chip for mimicking non-disruptive diffuse axonal injury underlying traumatic brain injury. Issue 23 (1st November 2022) - Pan, Xiaorong; Li, Jie; Li, Wei; Wang, Haofei; Durisic, Nela; Li, Zhenyu; Feng, Yu; Liu, Yifan; Zhao, Chun-Xia; Wang, Tong
Abstract : A microfluidic axon-on-a-chip (AoC) was designed to mimic the axonal injury underlying traumatic brain injury. Diffused axonal injury was modelled by adjusting the flow speed. Instant neuronal responses to the impacts can be resolved using the AoC. Abstract : Diffuse axonal injury (DAI) is the most severe pathological feature of traumatic brain injury (TBI). However, how primary axonal injury is induced by transient mechanical impacts remains unknown, mainly due to the low temporal and spatial resolution of medical imaging approaches. Here we established an axon-on-a-chip (AoC) model for mimicking DAI and monitoring instant cellular responses. Integrating computational fluid dynamics and microfluidic techniques, DAI was induced by injecting a precisely controlled micro-flux in the transverse direction. The clear correlation between the flow speed of injecting flux and the severity of DAI was elucidated. We next used the AoC to investigate the instant intracellular responses underlying DAI and found that the dynamic formation of focal axonal swellings (FAS) accompanied by Ca 2+ surge occurs during the flux. Surprisingly, periodic axonal cytoskeleton disruption also occurs rapidly after the flux. These instant injury responses are spatially restricted to the fluxed axon, not affecting the overall viability of the neuron in the acute stage. Compatible with high-resolution live microscopy, the AoC provides a versatile system to identify early mechanisms underlying DAI, offering a platform for screening effective treatments to alleviate TBI.